The role of the College of Education in facing the phenomenon of school dropout - A field study on faculty members at the College of Education, Brak Al-Shati - - Alsgaier, Mohamed Ali Mohamed (Journal of Educational and Psychological Sciences, 2020)
This study aims to know the role of the College of Education (Barak -Al-Shati) in the face of the phenomenon of school dropout, as well as to identify the social role of the college in facing the school dropout, and to know the reasons for the school dropout among college students, and the study relied on the descriptive analytical approach, and the questionnaire was taken as a tool for it for the purpose of collecting information from the community, which reached (23) singles only, and the sample of the study was (23) singles. By following the students ’achievement level and their discipline within the college, and family control is an important factor in preventing academic drop-out. In light of these results, the study recommends several recommendations, the most important of which are: The College of Education, Barak Al-Shati, should pay attention to developing students ’intellectual capabilities through various educational programs and activities, and work to raise the motivation for learning among students.